The methodological disorder in graduation theses - taibi, aissa (El Omda in Linguistics and Discourse Analysis, 2025)
Professors supervising graduation theses (Bachelor 's or Master 's ) face numerous challenges, some of which are related to methodological aspects, others to the language used, and others still to the improper application of t0he adopted research methods. Thes issues negatively impact the final quality of the theses. The dull final outcome of graduation theses highlights the necessity of reaffirming the importance of adhering to proper research methodology. This adherence is crucial to avoiding such disorders, which discourage readers from engaging with various studies end greatly distorts its results.